Arguing for the spirit in the language of the mind: a Maori practitioner's view of research and science : a thesis submitted for the degree of Doctor of Philosphy at Massey University - Barnes, Helen Moewaka (Massey University, 2008)
This thesis explores the ways that colonisation has resulted in Maori being cast as different and the other in Aotearoa/New Zealand. It challenges perceptions of relationships between Maori and western knowledge and between science and practice, drawing on a range of theorists, scholarly writings and multiple research and evaluation projects. The study examines how these perceptions, and the definitions arising from them, tend to compartmentalise Maori knowledge and research and, in doing so, serve non-Maori agendas more than they serve Maori aspirations. The thesis looks at the impacts that the world of the coloniser has had on our ways of knowing and ways of practising. Through illustrating initiatives that operate within Maori paradigms and collaborations between Maori and non-Maori, the development of equitable relationships is explored. Key findings are the need for a more inclusive understanding of knowledge and research practice in order to reframe the way we (coloniser and colonised) look at and express our understandings of the world and how these might be operationalised through research relationships. Part of the contribution of this thesis is to provide a framework for more equitable research relationships, focusing on non- Maori development. This is suggested as a counter to the constant examination and defining of Maori as different and in need of development.
Keywords: Maori research; Maori knowledge; Research relationships; Research practice; Fields of Research::370000 Studies in Human Society::379900 Other Studies In Human Society::379902 Indigenous studies